Pengaruh Massage Endorphin Dan Massage Counter Pressure Terhadap Tingkat Nyeri Kala I Fase Aktif Pada Ibu Bersalin Di Praktik Mandiri Bidan Sujtiati Kebo Jeruk Jakarta Barat Tahun 2021 - Jomima Batlajery; Hamidah Hamidah; Nina Primasari; Faudah Ashri Nurfurqoni (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Background : Labor pain can cause hyperventilation so that oxygen needs increase, increased blood pressure, and reduced intestinal motility and urinary vesika. This condition will stimulate an increase in catecholamines that can cause disturbances in the strength of uterine contractions resulting in uterine inertia. If labor pain is not overcome it will cause the occurrence of long partus. The old partus will be made for the mother and her fetus. Method : Pre Experiment research design using One Group Pretest-Posttest Design, the population is all maternity mothers in Sujtiati Midwife Self-Practice, a sample of 64 respondents with Purposive Sampling technique data analysis using chi square test and Wilcoxon test. Results : Massage endorphins and counter presur give a positive influence on maternity mothers it can be seen the value of alpa 0.003<0.05 is different from mothers who do not get the massage value alpa 0.104>0.05. Chi Square value 50,879 trust level 5% obtained data in the table chi value = 26.3 (50,879>26.3) and p<0.05/5%=0,000<0.05 this value indicates chi count> Chi table results show that there is a significant relationship between endhorpin massage and contuer pressure to the level of maternal pain during 1 phase of activation. Conclusion : Endorphin massage and counter presure have been shown to have a positive effect on maternity mothers and there is a significant association between endhorpin massage and contuer pressure to the level of pain of the mother giving birth during 1 active phase. Keywords : Massage endorphin, counter presure, maternal pain level of childbirth during 1 active phase.